Bank profitability : methodological country notes 2004 (OCDE, 2005)
This publication complements Bank Profitability: Financial Statements of Banks. The notes included in this volume were prepared to facilitate the comprehension and the interpretation of the statistics found in that volume and to provide a brief description of the activities of banks in each OECD country.